Disabilità e società Inclusione, autonomia, aspirazioni - Terraneo, Marco (Scienze e salute, 2021)
The book focuses on a well-established stream of research on disability which, both internationally and nationally, has proved fruitful in theoretical and analytical aspect, and was certainly fundamental in the process that led to the recognition of the rights of people with disabilities and the implementation of inclusive policies. The rigorous analysis present in all the chapters of the book also highlight the wide distance between the principles that guide the reflection on this issue, the policies for disability and the living conditions that people with disabilities experience daily. From the book emerges that the challenge is not merely the recognition of the rights of persons with disabilities but also making these rights enforceable. For this to be possible, both efficient and effective policies and a cultural change which recognizes disabled people "as part of human diversity and humanity" is necessary. This means placing at the center of discussion the aspirations and the empowerment of people with disabilities. The book is designed for scholars of disability, but also for social operators who work with disabled people.